Does AI Make Healthcare More Convenient? A Professional and Academic Perspective - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into the healthcare ecosystem is one of the most transformative developments of the 21st century. While much of...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Medical Ethics; Precision Medicine